2009
DOI: 10.3354/ame01305
|View full text |Cite
|
Sign up to set email alerts
|

Gross and net primary production: closing the gap between concepts and measurements

Abstract: We are living at a time when accurate knowledge of the magnitude of the drawdown of inorganic carbon by autotrophic metabolism is especially crucial to our understanding of global carbon cycling and the functioning of the global ecosystem. Since algae contribute approximately half of the planet's annual primary productivity, understanding the processes contributing to the net assimilation of CO 2 is critical. In this paper, we briefly discuss the range of approaches to measurements of aquatic photosynthesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…A negative correlation was found between ETR max and P B as revealed by the redundancy analysis (RDA), the ETR max being higher when P B was lower. This underlines another sink for electrons produced through nitrogen fixation for cyanobacteria, and nitrogen reduction for phytoplankton in general (Babin et al, 1996;Beardall et al, 2009). This electron sink could vary from day to day and on seasonnal scales, depending on nutrient availability, potentially confirming the existence of nutrient pulses in such ecosystem.…”
Section: Photosynthetic Parameters Regulationsmentioning
confidence: 99%
“…A negative correlation was found between ETR max and P B as revealed by the redundancy analysis (RDA), the ETR max being higher when P B was lower. This underlines another sink for electrons produced through nitrogen fixation for cyanobacteria, and nitrogen reduction for phytoplankton in general (Babin et al, 1996;Beardall et al, 2009). This electron sink could vary from day to day and on seasonnal scales, depending on nutrient availability, potentially confirming the existence of nutrient pulses in such ecosystem.…”
Section: Photosynthetic Parameters Regulationsmentioning
confidence: 99%
“…The debate concerning whether short-term 14 C relates to net or gross photosynthesis continues (Beardall et al 2009). Halsey et al (2010) showed that at low growth rates, newly fixed 14 C is mostly respired, which implies 14 C assimilation measures net photosynthesis, whereas at high growth rates, newly fixed 14 C enters biosynthetic pools, implying 14 C assimilation relates to gross photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The orthodox way to evaluate trophic energy is frequently complex and difficult to interpret (e.g., McNaughton et al, 1996;Corno et al, 2005;Beardall et al, 2009). Usual production assessments cannot differentiate alternative destinations for the fixed energy in the small scale.…”
Section: Indicatorsmentioning
confidence: 99%